Water Security and Public Health in Michika LGA: Assessing Microbial Contamination and Expanding Borehole Access - Umaru, Isaac John; Asare, Solomon Ossom; Omanchi, Emmanuel; Morgan, Akpan Usenobong; Olayemi, Abimbola Gbenga; Ametefe, Mathias Mawuli (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
Access to safe drinking water remains a critical public health challenge in many rural communities across Nigeria, and in Michika Local Government Area (LGA) of Adamawa State reliance on shallow wells and unprotected water sources has contributed to recurring outbreaks of waterborne diseases. This study assessed the safety and sustainability of water sources in Michika LGA by pursuing four objectives: evaluating microbial contamination—specifically the presence of Escherichia coli and total coliforms—and physicochemical parameters in wells and boreholes; conducting hydro-geophysical surveys to determine aquifer characteristics such as depth, thickness, and resistivity; utilizing Geographic Information System (GIS) tools to map borehole feasibility zones and identify contamination hotspots; and developing targeted recommendations for improving water safety and guiding future borehole expansion based on integrated data analysis. Water samples were collected from 20 wells and 15 boreholes across seven districts in Michika LGA, and microbial and physicochemical parameters were analyzed using standard laboratory procedures. Data were processed in SPSS v25, with descriptive statistics and ANOVA applied to compare contamination levels across districts and seasons. Hydro-geophysical surveys using Vertical Electrical Sounding (VES) were conducted to assess aquifer characteristics, while GIS mapping was employed to visualize borehole locations, contamination levels, aquifer productivity, and proximity to schools and clinics. Ethical approval was obtained from the State Health Research Ethics Committee, informed consent was secured from all participants, and water samples were anonymized and coded for confidentiality. The results revealed that 65% of wells tested positive for E. coli, with Zah and Moda districts recording the highest contamination levels (110 and 85 CFU/100 mL, respectively), whereas boreholes showed significantly lower microbial loads, with 80% falling within WHO safety limits. Physicochemical analysis indicated elevated turbidity in Minkisi and Garta (9.8 and 7.5 NTU), exceeding WHO guidelines. Hydro-geophysical data identified high-yield aquifer zones in Minkisi, Diaka, and Zah, with resistivity values above 120 Ωm and aquifer thickness exceeding 18 meters. GIS maps highlighted contamination hotspots overlapping with high population density zones and limited access to clinics, while districts such as Michika Town and Diaka, with safe boreholes and nearby infrastructure, were identified as optimal zones for expansion. Overall, this study highlights the urgent need for targeted water safety interventions in Michika LGA: wells remain highly vulnerable to microbial contamination, especially in densely populated districts, whereas boreholes located in high-yield aquifer zones offer a safer alternative and should be prioritized for development. GIS mapping proved instrumental in identifying contamination hotspots, aquifer feasibility, and infrastructure gaps, providing a data-driven roadmap for the Government of Adamawa State and the Michika community to improve water security, reduce disease burden, and guide sustainable borehole expansion.